Death-associated Protein Kinase 1 Mediates Ventilator-induced Lung Injury in Mice by Promoting Alveolar Epithelial Cell Apoptosis. (October 2020) - Wang, Yaxin; Yang, Yiyi; Chen, Lin; Xiong, Wei; Song, Limin; Li, Bo; Zhou, Ting; Pei, Lei; Yuan, Shiying; Yao, Shanglong; Shang, You
Abstract : Background: Alveolar epithelial cell apoptosis is implicated in the onset of ventilator-induced lung injury. Death-associated protein kinase 1 (DAPK1) is associated with cell apoptosis. The hypothesis was that DAPK1 participates in ventilator-induced lung injury through promoting alveolar epithelial cell apoptosis. Methods: Apoptosis of mouse alveolar epithelial cell was induced by cyclic stretch. DAPK1 expression was altered (knockdown or overexpressed) in vitro by using a small interfering RNA or a plasmid, respectively. C57/BL6 male mice (n = 6) received high tidal volume ventilation to establish a lung injury model. Adeno-associated virus transfection of short hairpin RNA and DAPK1 inhibitor repressed DAPK1 expression and activation in lungs, respectively. The primary outcomes were alveolar epithelial cell apoptosis and lung injury. Results: Compared with the control group, the 24-h cyclic stretch group showed significantly higher alveolar epithelial cell apoptotic percentage (45 ± 4% fold vs. 6 ± 1% fold; P < 0.0001) and relative DAPK1 expression, and this group also demonstrated a reduced apoptotic percentage after DAPK1 knockdown (27 ± 5% fold vs. 53 ± 8% fold; P < 0.0001). A promoted apoptotic percentage in DAPK1 overexpression was observed without stretching (49 ± 6% fold vs. 14 ± 3% fold; P < 0.0001). Alterations in B-cell lymphoma 2 and B-cell lymphoma 2–associated X are associated with DAPK1 expression. The mice subjected to high tidal volume had higher DAPK1 expression and alveolar epithelial cell apoptotic percentage in lungs compared with the low tidal volume group (43 ± 6% fold vs. 4 ± 2% fold; P < 0.0001). Inhibition of DAPK1 through adeno-associated virus infection or DAPK1 inhibitor treatment appeared to be protective against lung injury with reduced lung injury score, resolved pulmonary inflammation, and repressed alveolar epithelial cell apoptotic percentage (47 ± 4% fold and 48 ± 6% fold; 35 ± 5% fold and 34 ± 4% fold; P < 0.0001, respectively). Conclusions: DAPK1 promotes the onset of ventilator-induced lung injury by triggering alveolar epithelial cell apoptosis through intrinsic apoptosis pathway in mice. Abstract : In mice, high tidal volumes increased cyclic stretch, DAPK1 expression, and epithelial cell apoptosis. Inhibition of DAPK1 appeared to be protective against lung injury, reducing lung injury, inflammation, and apoptosis. DAPK1 triggers alveolar epithelial cell apoptosis and mediates ventilator-induced lung injury in mice.Supplemental Digital Content is available in the text.